Hyperelastic and elastic-plastic approaches for modelling uniaxial tensile performance of woven fabrics / Yahya, M.F. and Chen, X. - Yahya, Mohamad Faizul; Chen, Xi (Research Management Institute (RMI), 2010)
This article presents thefindings ofexperimental andfinite element simulation warp direction uniaxial tensile testing ofplain 1/1, 2/2 twill and 8 ends satin woven fabrics with respect to a wovenfabric model developed in IGES using UniverFilter. Woven fabrics have been specifically configured as a balanced weave thereby allowing systematic investigation of the effect of uniaxial tensile stress on the weave. Static automatic incrementation of large representative volume elements has enabled characterisation ofthe response oftwo-dimensional woven fabrics under uniaxial tensile stress with respect to hyperelastic and elastic-plastic material properties. Plain 1/1 and 8 ends satin woven fabrics were well-described by the hyperelastic model and the elastic-plastic model predicted extended strain percentages. The modelling indicates that satin woven fabric possesses the lowest strain distribution and compression stress in the unloaded weft direction compared to plain and twill woven fabrics.